Implementation of Programmatic Assessment: Challenges and Lessons Learned - Marjan Govaerts; Cees Van der Vleuten; Suzanne Schut (MDPI AG, 2022)
In the past few decades, health professions education programmes around the world have embraced the competency-based paradigm to guide the education and assessment of future healthcare workers [...]